Learning or leaning: Persistent and transitory spillovers from FDI - Ronald B. Davies; Michael J. Lamla; Marc Schiffbauer (ETH Zurich, KOF Swiss Economic Institute, 2016)
Using firm-level data for Jordan, we estimate the extent to which growth spillovers from foreign direct investment (FDI) to local firms stem from persistent learning ex- ternalities (i.e., they endure even after foreign investment leaves as knowledge has been transferred to local firms) or from transitory effects (e.g., demand increases which evap- orate following disinvestment). We find that they have a significant transitory nature, with employment and capital growth declining when FDI falls, particularly in down- stream industries supplied by locals. This suggests that if FDI-attracting policies are intended to promote sustainable growth, it may be more effective to attract and retain FDI via long-term structural policies, for instance, through low corporate tax rates rather than temporary tax holidays or through policies that strengthen the domestic absorptive capacity and linkages between foreign and local firms. It also suggests that FDI-led growth can increase a country's vulnerability to adverse global shocks in that the productivity gains of domestic firms will be partly reversed with the disinvestment of multinational firms.
Keywords: F23; F16; 330; FDI; Spillovers